Effectiveness of the Integrated Dengue Education and Learning (iDEAL) module in improving the knowledge, attitude, practice, environmental cleanliness index, and dengue index among schoolchildren: a randomised controlled trial protocol - Dapari, Rahmat; Muniandy, Kalaivani; Fattah Azman, Ahmad Zaid; Abu Bakar, Suhaili; Mohd Desa, Mohd Nasir; Hwa, Lim Chee; Singh Sandhu, Sukhvinder; Mustapha, Nooreen Farzana; Mohd Rosli, Norazman; Ahmad Zamzuri, Mohd ‘Ammar Ihsan; Hassan, Mohd Rohaizat; Che Dom, Nazri; et al. (Public Library of Science, 2024)
Background Dengue is a mosquito-borne disease caused by four distinct, closely related dengue viruses (DENV). Global dengue incidence has markedly increased in the past decades. The World Health Organization reported that cases increased from 505,430 in 2000 to 5.2 million in 2019. Similarly, the total dengue cases in Malaysia increased from 7,103 in 2000 to a peak of 130,101 in 2019. Knowledge, attitude, and practice (KAP) remain the most effective dengue prevention and control tools. Furthermore, school-based health education is key to enhancing knowledge and raising awareness of the seriousness of dengue among schoolchildren and transferring knowledge and practice from classrooms to homes. Thus, it is necessary to plan an integrated module for the primary prevention of dengue infection, specifically among schoolchildren.